2010
DOI: 10.1159/000299179
|View full text |Cite
|
Sign up to set email alerts
|

5-Year Prospective Follow-Up of Artisan Phakic Intraocular Lenses for the Correction of Myopia, Hyperopia and Astigmatism

Abstract: Aim: To determine the efficacy and safety of Artisan phakic intraocular lenses (IOLs) for refractive error correction. Methods: A prospective study was conducted on patients undergoing Artisan phakic IOL implantation for myopia, hyperopia or astigmatism from 2002 to 2008. Visual acuity, manifest refractive spherical equivalent (MRSE), endothelial cell counts and higher order aberrations were recorded pre- and postoperatively. Results: One hundred and fifty-one (84 patients) myopic (mean MRSE –11.2 ± 4.1 D) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 53 publications
0
19
0
2
Order By: Relevance
“…However, the rigid Artisan toric pIOL has been extensively studied. [3][4][5][6][7][8][9][10][11][12][13][14] In a European multicenter clinical study, Dick et al 4 found no loss of CDVA and a gain of 1 or more lines from the preoperative CDVA in 65.7% of eyes; in 88.6% of eyes, the UDVA was 20/40 or better. The spherical and astigmatic errors were significantly reduced in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the rigid Artisan toric pIOL has been extensively studied. [3][4][5][6][7][8][9][10][11][12][13][14] In a European multicenter clinical study, Dick et al 4 found no loss of CDVA and a gain of 1 or more lines from the preoperative CDVA in 65.7% of eyes; in 88.6% of eyes, the UDVA was 20/40 or better. The spherical and astigmatic errors were significantly reduced in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The Artisan concept has stood the test of time for its iris-claw fixation principle as well as the clinical long-term safety and efficacy results. [2][3][4]6,12,13 These results have been well documented for the spherical Artiflex IOL and have been compared with those of its predecessor, the rigid (PMMA) Artisan IOL. 9,[14][15][16][17] The foldable Artiflex toric pIOL has 2 main advantages over the rigid Artisan toric type.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The toric Implantable Collamer Lens collagen copolymer phakic intraocular lens (pIOL) (Staar Surgical Co.) has been used to safely and reliably correct moderate to high myopia and astigmatism. [12][13][14][15][16] Given that the progression of corneal thinning and ectasia in PMD, like keratoconus, tends to stabilize in the third or fourth decade of life, 17 toric pIOL implantation may be another option for the surgical correction of myopic astigmatism in this setting. Studies [18][19][20] are beginning to show the safety and efficacy of this treatment modality in keratoconus.…”
Section: Resultsmentioning
confidence: 99%
“…Toric Implantable Collamer Lens pIOLs have been validated in many studies as safe and effective for the correction of moderate to high myopic astigmatism. [12][13][14][15][16] Randomized prospective comparisons between toric pIOL implantation and excimer laser vision correction 24,25 show better safety, predictability, and stability profiles with pIOLs. Based on these studies, surgeons are now using toric pIOLs to successfully treat myopic astigmatism in keratoconus and keratoconus-suspect eyes.…”
Section: Discussionmentioning
confidence: 99%